Space and place for health and care. (15th December 2020) - Roxberg, Åsa; Tryselius, Kristina; Gren, Martin; Lindahl, Berit; Werkander Harstäde, Carina; Silverglow, Anastasia; Nolbeck, Kajsa; James, Franz; Carlsson, Ing-Marie; Olausson, Sepideh; Nordin, Susanna; Wijk, Helle
ABSTRACT: Purpose : This discussion paper aims to contribute to a greater understanding of the state of the art of research engaged with conceptual matters of space and place for health and care. Method : The authors, who represent a variety of academic disciplines, discuss and demonstrate the conceptual recognition of space and place in research in health and caring sciences building upon own work and experience. Results : To explore the concepts of space and place for health and care is a research pursuit of utmost importance, and should be made through transdisciplinary research collaborations, whereby spatial theories from various disciplines could be communicated to cultivate truly novel and well-informed research. Furthermore, engaging with relational and topological perceptions of space and place poses methodological challenges to overcome in future research on health and care. Conclusions : We argue that there is a need for accelerating spatially informed research on health and care that is informed by current theories and perspectives on space and place, and transdisciplinary research collaborations are a means to achieving this.